2022
DOI: 10.1111/pce.14513
|View full text |Cite
|
Sign up to set email alerts
|

bHLH57 confers chilling tolerance and grain yield improvement in rice

Abstract: Chilling stress has become a major limiting factor that reduces crop productivity worldwide. In this study, we identified a new gene bHLH57, whose product enhances chilling tolerance in rice at diverse developmental stages. bHLH57 was mainly expressed in leaves and anthers, and its protein was targeted to the nucleus. Overexpression of bHLH57 enhanced chilling tolerance by increasing trehalose synthesis, whereas its mutants by CRISPR/Cas9‐mediated mutagenesis were more sensitive to chilling and had reduced tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…128 Of note, Zhang et al identified a new bHLH regulator, named OsbHLH57, involved rice chilling tolerance and increased grain yield under normal and chilling conditions. 121,122 In banana (Musa acuminate), the overexpression of MaICE1 has been shown to confer cold tolerance. 206 In recent years, there has been more comprehensive research on the interactors of MaICE1, both in vitro and in vivo.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
See 1 more Smart Citation
“…128 Of note, Zhang et al identified a new bHLH regulator, named OsbHLH57, involved rice chilling tolerance and increased grain yield under normal and chilling conditions. 121,122 In banana (Musa acuminate), the overexpression of MaICE1 has been shown to confer cold tolerance. 206 In recent years, there has been more comprehensive research on the interactors of MaICE1, both in vitro and in vivo.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
“…Additionally, OsWRKY76 interacts with OsbHLH148 and coordinately upregulates the expression of OsDREB1B to enhance cold tolerance . Of note, Zhang et al identified a new bHLH regulator, named OsbHLH57, involved rice chilling tolerance and increased grain yield under normal and chilling conditions. , …”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
“…Phenotypic, biochemical, physiological, molecular and cellular understanding of chilling tolerance in rice and novel approaches to speed up molecular design breeding for cold tolerance in rice varieties have been previously reviewed (Li, Zhang, Chong, et al, 2022). However, the ultimate solution to expand rice‐planting to northern areas depends largely on the development of cold/chilling‐tolerant cultivars, which needs mining and exploiting of key genes or alleles Zhang et al reported in this issue that bHLH57 can enhance trehalose synthesis, reactive oxygen species metabolism and CBFs/DREBs‐dependent pathways, acting as a positive regulator of rice chilling tolerance, and that bHLH57 can enhance seed setting rate and seed size, thus increasing grain yield (L. Zhang, Xiang, et al, 2023). Therefore, bHLH57 is a potential target for future breeding for high‐yielding, chilling‐tolerant rice varieties.…”
Section: Abiotic Resilience Of Ricementioning
confidence: 99%
“…However, O. rufipogon (the ancestor of Asian rice) is perennial. Due to “one‐sow‐one‐harvest” nature, annual rice is not sustainable in many aspects, and particularly vulnerable to changing climates; Due to a more extensive root systems and greater assimilate reserves, perennial rice can better cope with abiotic stress and grow better in more marginal landscapes (Zhang, Huang, et al, 2023). Currently three perennial rice cultivars (PR23, PR25, and PR107) produced by crossing of annual Asian rice with its perennial African relative ( O. longistaminata ) have been released in China.…”
Section: Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation